1998
DOI: 10.1002/(sici)1096-9861(19981123)401:3<411::aid-cne8>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the tectal zone on the distribution of synaptic boutons in the brainstem of goldfish

Abstract: This study investigated whether the topographic differences in the functional properties of the tectal motor map of goldfish are related to particular patterns of connections with downstream structures. With this aim, the distribution of synaptic boutons in the mesencephalic and rhombencephalic structures was studied after discrete injections of the tracer biotinylated dextran amine were placed at separate sites along the tectal anteroposterior axis. Irrespective of the location of the injection site, the bout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…A reciprocal connectivity of the torus semicircularis with the optic tectum has been thoroughly reported previously in fish (Grover & Sharma, 1979, 1981Luiten, 1981;Fiebig et al, 1983;Schlussman et al, 1990;Herrero et al, 1998a). In nonelectroreceptive teleosts, the torus semicircularis is involved in processing the acoustic and lateral line signals (Lu & Fay, 1993;Wubbels & Schellart, 1997;Meek & Nieuwenhuys, 1998).…”
Section: Location Of Tectal Afferentsmentioning
confidence: 77%
See 1 more Smart Citation
“…A reciprocal connectivity of the torus semicircularis with the optic tectum has been thoroughly reported previously in fish (Grover & Sharma, 1979, 1981Luiten, 1981;Fiebig et al, 1983;Schlussman et al, 1990;Herrero et al, 1998a). In nonelectroreceptive teleosts, the torus semicircularis is involved in processing the acoustic and lateral line signals (Lu & Fay, 1993;Wubbels & Schellart, 1997;Meek & Nieuwenhuys, 1998).…”
Section: Location Of Tectal Afferentsmentioning
confidence: 77%
“…However, the approach of these works to tectal connectivity did not fully allow for differences in the characteristics by which different tectal zones evoke movements and the possibility that each zone could maintain a particular wiring in its efferents and afferents with distinct brain structures. Indeed, recent studies have shown that tectal efferent connectivities with the mesencephalic and rhombencephalic reticular formation are different depending on the functional properties of each tectal zone (Herrero et al, 1998a;Moschovakis et al, 1998;Perez-Perez et al, 2000). Furthermore, morphological studies of afferents to different tectal zones, which were not functionally identified, showed both differences in the pattern of projections to the rostral and caudal tectum (Grover & Sharma, 1981) and a topographical organization of afferents from the nucleus isthmi to the tectum (Sakamoto et al, 1981;Dunn-Meynell & Sharma, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…MeLr and MeLc extend elaborate dendrites into the deeper layers of the tectum. Here, the cell bodies of tectofugal projection neurons are situated (Meek and Schellart, 1978;Nguyen et al, 1999), which, in other teleosts, have been reported to send a predominantly ipsilateral and excitatory projection to the nMLF (Bosch and Paul, 1993;Herrero et al, 1998a;Niida et al, 1998;Zompa and Dubuc 1998a,b;Isa and Sasaki, 2002;Torres et al, 2002;Perez-Perez et al, 2003). MeLr and MeLc extend axons into the spinal cord, arborizing predominantly in its rostral segments, in which their axon terminals colocalize with motor neurons and interneurons .…”
Section: Discussionmentioning
confidence: 99%
“…As we modeled a left eye, this actuates the lateral rectus muscle. The exponential rise of Equation (29) (for experimental evidence, see Figures 7, 8 of Herrero et al, 1998 ) is seen in the r direction; as r increases, so the connection strength to the SBG channel rises exponentially. The connection strength is greatest along the center line, for a value of ϕ which corresponds to a purely leftward movement.…”
Section: Resultsmentioning
confidence: 96%
“…The spatial aspect of the transform is thought to be implemented by a weight-mapping (Arai et al, 1994 ; Tabareau et al, 2007 ). Although there is no definitive experimental proof for such a mapping, there exists evidence for spatially variable synapse density (Herrero et al, 1998 ; Moschovakis et al, 1998 ) and connection density (Grantyn et al, 2002 ) and we therefore adopt the idea. Arai and co-workers trained a 20 by 20 neural network model of the superior colliculus to discover the weight map under the assumption of 2D Gaussian activation profiles (Arai et al, 1994 )—that is, they assumed that the activity in superior colliculus for any saccade was a size-invariant 2D Gaussian hill of activity.…”
Section: Methodsmentioning
confidence: 99%